The Effect of the Number of MSME, Number of Workers, MSME Investment on Regional Economic Growth in West Nusa Tenggara Province - Irawati, Irawati; Gusti Ayu Arini; Satarudin, Satarudin (Tinta Emas Institute, 2023)
This study aims to analyse the effect of the number of MSMEs, the number of MSME workers, MSME investment on economic growth in West Nusa Tenggara Province. This type of research is quantitative descriptive research, the type of data used in this study is quantitative data and is panel data, namely the time series data used is data for the 2017-2021 period for 5 years while the cross-section data includes data from 10 districts / cities in West Nusa Tenggara Province. The data source in this study is secondary data. The collection technique used in the research is the documentation method or library research. From the test results together show that the number of MSMEs, the number of MSME workers, MSME investment has a significant effect on economic growth in West Nusa Tenggara Province (NTB), and partial testing shows that the number of MSMEs, MSME labour, and MSME investment have no significant effect on economic growth in NTB Province.